A cerium-vanadium bimetallic hollow nanocolumn array type electrocatalytic material, a preparation method and application thereof

CN117904672BActive Publication Date: 2026-10-09TIANJIN BOHAI VOCATIONAL TECHN COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410088685.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-22
Publication Date
2026-10-09
Estimated Expiration
2044-01-22

AI Technical Summary

Technical Problem

值得注意的是,现有的电解水催化剂(包括自支撑式电催化剂)为OER或HER单功能催化剂,OER和HER双功能电催化剂报道较少,这主要源于OER和HER反应机理和过程上的巨大差异

Benefits of technology

[0027] (1) The cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material prepared in this invention has a three-dimensional porous substrate with good conductivity, which can ensure the efficient transport of electrons and matter; the hollow nanopillar array structure can ensure the full exposure of active sites and the release and transport of gaseous products; the bimetallic synergistic effect and the large number of oxygen vacancies brought by etching can promote the improvement of catalytic activity. Therefore, as an OER and HER electrocatalyst, it can significantly improve the efficiency and stability of water electrolysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117904672B_ABST
    Figure CN117904672B_ABST
Patent Text Reader

Abstract

The application provides a cerium-vanadium bimetallic hollow nanocolumn array type electrocatalytic material and a preparation method and application thereof, and comprises a substrate and a composite loaded on the substrate; the composite forms a hollow nanocolumn array type structure on the substrate, and the composite comprises CeO2, V8C7 and V2O5. A vanadium-based metal organic framework V-MOF nanocolumn array is obtained on the substrate through an in-situ growth method; then based on the principle that the coordination combination energy of cerium and a ligand is lower and the formed structure is more stable, cerium salt is used for etching to construct a cerium-vanadium MOF hollow nanocolumn array; finally, high-temperature carbonization is carried out under an argon atmosphere to obtain the cerium-vanadium bimetallic hollow nanocolumn array type electrocatalytic material. The cerium-vanadium bimetallic hollow nanocolumn array type electrocatalytic material has a dual function of catalyzing oxygen evolution reaction and hydrogen evolution reaction, and has high catalytic activity and good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water electrolysis for hydrogen production technology, and in particular relates to a cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material, its preparation method, and its application. Background Technology

[0002] Developing sustainable green energy is a crucial way to alleviate the increasingly severe global energy and environmental crisis. Hydrogen energy, with its high energy density and zero carbon emissions, is considered one of the most promising alternatives to traditional fossil fuels. Compared with other technologies, electrochemical water splitting is more attractive for large-scale hydrogen production due to its reliability and sustainability. Unfortunately, the large-scale commercial application of electrochemical water splitting is limited by several factors, such as the overpotential required to drive the overall water electrolysis being much higher than the theoretical value (1.23V) and the poor stability of electrode materials. Therefore, it is necessary to develop efficient and durable electrocatalysts to reduce the overpotentials of the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) at the anode and cathode, thereby improving the efficiency of water electrolysis. To date, ruthenium / iridium-based and platinum-based noble metal materials are recognized as high-performance OER and HER catalysts, respectively. However, the scarcity and poor stability of these materials severely hinder their commercial application. Therefore, designing and preparing non-noble metal electrocatalysts to accelerate water electrolysis has significant practical implications.

[0003] For many years, researchers have focused on developing transition metal compounds based on cobalt, nickel, and iron as alternative catalysts for water electrolysis. For example, transition metal-based oxides, hydroxides, phosphates, and hydroxides have exhibited excellent OER activity, while transition metal-based phosphides, selenides, sulfides, and nitrides have shown high catalytic activity in HER. However, the electrolytic performance and stability of these materials are far from meeting practical needs, necessitating further development and exploration.

[0004] On the other hand, existing water electrolysis catalysts are mainly in powder form, requiring the application of polymer binders to coat them onto a conductive substrate during electrochemical testing. This approach introduces several negative effects on the electrocatalytic reaction: reduced catalyst loading, resulting in limited active sites; higher interfacial resistance between the catalyst layer and the conductive substrate, affecting electron transfer efficiency; and weak adhesion between the catalyst layer and the substrate, making them prone to detachment during electrochemical processes. In contrast, constructing self-supported electrocatalysts by introducing catalytically active components onto porous conductive substrates such as nickel foam (NF) and carbon cloth avoids these problems. Another advantage of self-supported electrocatalysts is that their catalytic activity and stability can be further improved by controlling the morphology and microstructure of the catalyst layer on the porous substrate surface. For example, our research group previously prepared two-dimensional nickel-iron metal-organic framework (MOF) nanosheets on carbon cloth using an in-situ hydrothermal method, and then constructed a nickel-iron-phosphide nanosheet-based self-supported electrocatalyst using vapor deposition, which exhibited excellent OER performance in alkaline solution [Chai RQ, Zhou TQ, Sun DL, et al. Bimetallic-MOF derived nickel-iron phosphide nanosheets on carbon cloth for efficacious oxygen evolution reaction. International Journal of Hydrogen Energy, 2022, 47, 36129-36138]. Furthermore, an ideal electrocatalyst should possess dual functionality in catalyzing both HER and OER in the same electrolyte solution, thereby improving the overall efficiency of water electrolysis. It is noteworthy that existing water electrolysis catalysts (including self-supported electrocatalysts) are monofunctional OER or HER catalysts, with fewer reports on bifunctional OER and HER electrocatalysts. This is mainly due to the significant differences in the reaction mechanisms and processes of OER and HER. Based on the above discussion, it is clear that developing bifunctional self-supporting non-precious metal catalysts that can catalyze both OER and HER is a key issue that urgently needs to be addressed by researchers. Summary of the Invention

[0005] In view of this, the present invention aims to at least partially solve the bottleneck problems in the related technologies, and proposes a cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material, its preparation method and application, to prepare an electrolytic material with high catalytic activity and good stability, and the catalytic material has dual functions of catalyzing OER and HER.

[0006] To achieve the above objectives, the technical solution of the present invention is implemented as follows:

[0007] A cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material includes a substrate and a composite supported on the substrate. The composite forms a hollow nanopillar array structure on the substrate. The composite includes cerium oxide (CeO2), vanadium heptacarbide (V8C7), and vanadium pentoxide (V2O5).

[0008] In some embodiments, the molar ratio of CeO2, V8C7 and V2O5 is (3-15):(10-40):(30-70), preferably (5-10):(20-30):(40-60).

[0009] In some embodiments, the substrate is nickel foam NF.

[0010] In some embodiments, the total loading of CeO2, V8C7, and V2O5 on the substrate is 1–5 mg cm⁻¹. -2 Preferably 2-3 mg cm -2 .

[0011] A method for preparing a cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material includes the following steps:

[0012] (1) The substrate nickel foam NF is placed in a vanadium-based synthesis solution for in-situ growth. The reaction is carried out at 150-170℃ for 45-75h, which can form a vanadium-based metal-organic framework V-MOF nanopillar array on the substrate.

[0013] (2) The substrate loaded with V-MOF nanopillar array was placed in an aqueous solution of cerium salt and etched after standing for 6 to 18 hours to obtain a substrate-supported CeV-MOF hollow nanopillar array.

[0014] (3) The substrate loaded with CeV-MOF hollow nanopillar array was placed in a muffle furnace and calcined at 550-650℃ for 2-5 h under an argon atmosphere to obtain cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material.

[0015] The vanadium-based synthesis solution comprises vanadium oxysulfate, ligands, and deionized water;

[0016] The ligand is terephthalic acid or aminoterephthalic acid;

[0017] The cerium salt is any one of cerium ammonium nitrate, cerium nitrate, cerium chloride, and cerium sulfate.

[0018] In some embodiments, the molar ratio of vanadium sulfate, ligand and deionized water is 1:1:(3500-4500).

[0019] In some embodiments, the concentration of cerium ions in the aqueous solution of the cerium salt is greater than 0.3 mol / L. -1And less than 0.7 mol L -1 Preferably, it is 0.5–0.6 mol / L. -1 .

[0020] In some embodiments, the cerium salt is cerium ammonium nitrate.

[0021] In some embodiments, the substrate has a size of (0.5-10)*(0.5-10)cm and a thickness of 0.1-10mm.

[0022] In some embodiments, the calcination process in step (3) is a programmed temperature rise, with a heating rate of 2°C / min. -1 .

[0023] A cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material has dual functions of catalyzing OER and HER, and can be used as an OER and HER catalyst during water electrolysis under alkaline conditions.

[0024] All raw materials involved in this invention are obtained through commercial purchase, and all equipment used is well known to those skilled in the art.

[0025] In this invention, the vanadium-based synthesis solution uses vanadium oxysulfate, ligands (terephthalic acid or aminoterephthalic acid), and deionized water as reactants to obtain a V-MOF nanopillar array on a substrate NF via in-situ growth. Then, based on the principle that cerium has a lower coordination energy with the ligand and forms a more stable structure, a CeV-MOF hollow nanopillar array is constructed on the substrate through cerium salt etching. Finally, high-temperature carbonization under an argon atmosphere yields a cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material. The characteristics of this electrocatalytic material enable it to catalyze both OER and HER.

[0026] Compared with existing technologies, the cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material, its preparation method, and its application described in this invention have the following advantages:

[0027] (1) The cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material prepared in this invention has a three-dimensional porous substrate with good conductivity, which can ensure the efficient transport of electrons and matter; the hollow nanopillar array structure can ensure the full exposure of active sites and the release and transport of gaseous products; the bimetallic synergistic effect and the large number of oxygen vacancies brought by etching can promote the improvement of catalytic activity. Therefore, as an OER and HER electrocatalyst, it can significantly improve the efficiency and stability of water electrolysis.

[0028] (2) The cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material prepared in this invention can significantly reduce the overpotential of electrocatalytic water splitting as a bifunctional catalyst for OER and HER, and has good stability.

[0029] (3) The preparation method of the present invention is simple and easy to implement; the materials used are inexpensive; the solvent used is deionized water, which reduces the use of organic solvents, is green and environmentally friendly, and is suitable for industrial production. Attached Figure Description

[0030] Figure 1 The image shows a scanning electron microscope (SEM) image of V-MOF / NF obtained in Example 1 of this invention.

[0031] Figure 2 The image shown is a SEM image of CeV-MOF / NF obtained in Example 1 of this invention.

[0032] Figure 3 This is a SEM image of CeV-HNA / NF obtained in Example 1 of the present invention;

[0033] Figure 4 The image shows the X-ray diffraction (XRD) pattern of CeV-HNA / NF obtained in Example 1 of this invention.

[0034] Figure 5 The OER polarization curves of CeV-HNA / NF, CeV-MOF / NF, V-NA / NF, CeO2 / NF and IrO2 obtained in Example 1 of the present invention are shown.

[0035] Figure 6 The HER polarization curves of CeV-HNA / NF, CeV-MOF / NF, V-NA / NF, CeO2 / NF and PtC obtained in Example 1 of the present invention are shown.

[0036] Figure 7 The HER it curve of CeV-HNA / NF obtained in Example 1 of this invention;

[0037] Figure 8 The voltammetric curves of the complete water hydrolysis of CeV-HNA / NF and Pt / C∥IrO2 prepared in Example 1 of this invention are shown.

[0038] Figure 9 This is a water hydrolysis curve of CeV-HNA / NF prepared in Example 1 of the present invention;

[0039] Figure 10 The image shows the SEM plot of CeV-MOF / NF obtained in Comparative Example 1;

[0040] Figure 11 The image shows the SEM plot of CeV-MOF / NF obtained in Comparative Example 2;

[0041] Figure 12The OER polarization curves of CeV-HNA / NF obtained in Example 1 of this invention and CeNiFe / NF, CeCo / NF and VCo / NF catalysts obtained in Comparative Examples 3 to 5 are shown.

[0042] Figure 13 The images show the HER polarization curves of the CeV-HNA / NF catalyst obtained in Example 1 of this invention, as well as the CeNiFe / NF, CeCo / NF, and VCo / NF catalysts obtained in Comparative Examples 3 to 5. Detailed Implementation

[0043] Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as commonly understood by those skilled in the art. Unless otherwise specified, the experimental reagents used in the following embodiments are conventional biochemical reagents; and the experimental methods described are conventional methods.

[0044] The present invention will now be described in detail with reference to the embodiments and accompanying drawings.

[0045] Example 1

[0046] Preparation method of cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material. The cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material prepared in Example 1 is referred to as CeV-HNA / NF.

[0047] I. Material Preparation:

[0048] The steps are as follows:

[0049] (1) Dissolve 0.122g vanadium oxysulfate (0.75mmol) and 0.125g terephthalic acid (0.75mmol) in 54mL (3mol) of deionized water (the molar ratio of the three is 1:1:4000), and sonicate at room temperature for 30min to obtain a light green transparent vanadium-based synthesis solution.

[0050] The vanadium-based synthesis solution was transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene (PTFE). The substrate NF (0.5 mm thick, 1 x 2 cm in size) was vertically immersed in the vanadium-based synthesis solution and heated at 160°C for 48 hours, then allowed to cool naturally to room temperature. After removal, the material was washed several times with deionized water and anhydrous ethanol. Specifically, it was soaked in deionized water in a beaker for 12 hours, then the water was replaced and the soaking continued for another 12 hours. This process was repeated twice to remove unreacted substances. Then, it was soaked in ethanol for 12 hours, then the ethanol was replaced and the soaking continued for another 12 hours. This process was repeated twice to remove the deionized water from the previous step. Finally, it was dried at 60°C for 12 hours to obtain the V-MOF nanopillar array supported by the substrate NF, i.e., V-MOF / NF.

[0051] (2) Dissolve 4.122 g of cerium ammonium nitrate in 15 mL of deionized water (molar concentration of 0.5 mol / L). -1 Then, V-MOF / NF is vertically immersed in the above cerium ammonium nitrate solution and allowed to stand for 12 hours. After being cleaned with deionized water, it is dried at 60°C for 12 hours to form a CeV-MOF hollow nanopillar array, namely CeV-MOF / NF, on the NF substrate.

[0052] (3) Finally, CeV-MOF / NF was loaded into a ceramic boat, placed in a muffle furnace, and then purged with argon for 1 hour to remove air, and then heated at 2℃ for 1 minute. -1 The heating rate was increased to 600℃ and held for 2 hours to obtain a cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material, namely CeV-HNA / NF.

[0053] II. CeV-HNA / NF as a bifunctional catalyst for OER and HER:

[0054] Electrocatalytic performance testing was conducted using a CHI760E electrochemical workstation with a 1 mol / L electrolyte. -1 A potassium hydroxide solution with an effective electrode area of ​​1 cm². 2 OER and HER measurements employed a three-electrode system, with Ag / AgCl as the reference electrode, a carbon rod as the counter electrode, and CeV-HNA / NF as the working electrode. The linear sweep voltammetry scan rate was 10 mV / s. -1 The electrode potentials are all converted to the reversible hydrogen electrode potential (RHE) according to the following formula:

[0055] E RHE =E(Ag / AgCl)+0.0591*pH+0.197V

[0056] E(Ag / AgCl) is the voltage actually measured relative to the Ag / AgCl electrode as a reference electrode, 0.197V is the standard potential of the Ag / AgCl reference electrode used, and pH is the acidity or alkalinity of the electrolyte used.

[0057] Commercially available IrO2 and PtC were used as control samples in the OER and HER tests, respectively, and CeV-MOF / NF, V-NA / NF, and CeO2 / NF were also used as control samples.

[0058] Preparation method of V-NA / NF:

[0059] First, prepare V-MOF / NF:

[0060] Its preparation process is the same as that in step (1) of Example 1;

[0061] Then, V-NA / NF was prepared:

[0062] The preparation process is the same as that in step (3) of Example 1, that is, V-MOF / NF is loaded into a ceramic boat, placed in a muffle furnace, and then purged with argon for 1 hour to remove air, and then heated at 2℃ for 1 minute. -1 The heating rate was increased to 600℃ and held for 2 hours to obtain V-NA / NF.

[0063] Preparation method of CeO2 / NF:

[0064] Dissolve 4.112 g of cerium ammonium nitrate in 15 mL of deionized water (molar concentration 0.5 mol / L). -1 Then, the substrate NF (thickness 0.5 mm, size 1*2 cm) is vertically immersed in the above cerium ammonium nitrate solution and left to stand for 12 hours; after being cleaned with deionized water, it is dried in a drying oven at 60°C for 12 hours.

[0065] Then, the obtained sample was subjected to high-temperature calcination, the process of which was the same as the calcination process in step (3) of Example 1, that is, the sample was placed in a ceramic boat, placed in a muffle furnace, and then purged with argon gas for 1 hour to remove air, and then calcined at 2°C for 1 minute. -1 The heating rate was increased to 600℃ and held for 2 hours to obtain CeO2 / NF.

[0066] The water splitting performance was evaluated using a dual-electrode system, with CeV-HNA / NF serving as both the anode and cathode. A commercially available electrolyzer using PtC and IrO2 as the anode and cathode was used as a control, operating at 10 mV s. -1 The catalyst was tested and its overall water-splitting stability was investigated using the chronoamperometry method.

[0067] Figure 1 This is a SEM image of the V-MOF / NF prepared in Example 1. As can be seen, cubic columnar MOF grains are deposited on the NF, covering the substrate NF.

[0068] Figure 2 This is a SEM image of the CeV-MOF / NF prepared in Example 1. As can be seen, after etching with cerium salt solution, the CeV-MOF nanopillar array has become a hollow structure.

[0069] Figure 3 This is a SEM image of the CeV-HNA / NF prepared in Example 1. It can be seen that the morphology of the CeV-HNA / NF obtained after calcination is similar to that of CeV-MOF / NF, but the wall thickness of the hollow nanopillars in CeV-HNA / NF is reduced.

[0070] Figure 4The image shows the XRD pattern of the CeV-HNA / NF prepared in Example 1. The figure clearly shows characteristic peaks for CeO2, V8C7, and V2O5, indicating that the prepared material is a composite of CeO2, V8C7, and V2O5.

[0071] Figure 5 The OER test results are for CeV-HNA / NF, CeV-MOF / NF, V-NA / NF, CeO2 / NF, and IrO2 prepared in Example 1 of this invention. Figure 5 It can be seen that, compared with CeV-MOF / NF, V-NA / NF, CeO2 / NF and commercial IrO2 catalysts, CeV-HNA / NF exhibits better performance at 50 mA cm⁻¹. -2 The overpotential is smaller (220mV), indicating that CeV-HNA / NF has the best OER performance.

[0072] Figure 6 The results show the HER test results for CeV-HNA / NF, CeV-MOF / NF, V-NA / NF, CeO2 / NF, and PtC prepared in Example 1 of this invention. Figure 6 It can be seen that, compared with CeV-MOF / NF, V-NA / NF, CeO2 / NF and commercial Pt / C catalysts, CeV-HNA / NF exhibits superior performance at 50 mA cm⁻¹. -2 The smaller overpotential (125mV) indicates that CeV-HNA / NF has the best HER performance.

[0073] Figure 7 The CeV-HNA / NF prepared in Example 1 was subjected to an amplitude of 100 mA cm⁻¹. -2 The it curve under high current density. (From...) Figure 7 It can be seen that CeV-HNA / NF can maintain a stable current density within 300 hours, demonstrating excellent stability.

[0074] Figure 8 and Figure 9 This is a diagram showing the overall water electrolysis performance of the CeV-HNA / NF prepared in Example 1, used simultaneously as the anode and cathode of a water electrolyzer. Figure 8 It can be seen that CeV-HNA / NF can drive water electrolysis to 10mA cm⁻¹ at 1.52V. -2 Superior performance to commercially available Pt / C∥IrO2; by Figure 9 It can be seen that CeV-HNA / NF at 100mA cm -2 It can maintain water electrolysis stability for 150 hours under high current density, showing its potential for practical application.

[0075] The CeV-HNA / NF obtained in Example 1 possesses a highly conductive three-dimensional porous substrate, ensuring efficient electron and mass transport; its hollow nanopillar array structure guarantees sufficient exposure of active sites and the release and transport of gaseous products; the bimetallic synergistic effect and etching-induced oxygen vacancies further enhance catalytic activity. Therefore, as an OER and HER electrocatalyst, it can significantly improve the efficiency and stability of water electrolysis, which is evident in… Figures 5-9 The electrochemical performance was confirmed as shown. When CeV-HNA / NF is used as both the anode and cathode of the electrolyzer, it can drive the electrolysis of water to 10 mA cm⁻¹ at 1.52 V. -2 It outperforms commercially available Pt / C∥IrO2 and can be tested at 100 mA cm⁻¹. -2 It maintains the stability of electrolyzed water for 150 hours under high current density.

[0076] Example 2:

[0077] The preparation process of CeV-HNA / NF differs from that in Example 1 in that the molar concentration of cerium ammonium nitrate solution was adjusted to 0.4 mol / L during the etching process. -1 3.302 g of cerium ammonium nitrate was dissolved in 15 mL of deionized water, with other steps identical to those in Example 1. The electrochemical properties of the prepared electrocatalytic material were tested using the same procedure as in Example 1. The results showed that when CeV-HNA / NF was used simultaneously as both the anode and cathode of the electrolyzer, it could drive water electrolysis to 10 mA cm⁻¹ at 1.65 V. -2 It outperforms commercially available Pt / C∥IrO2 and can be tested at 100 mA cm⁻¹. -2 It can maintain the stability of electrolyzed water for 150 hours under high current density.

[0078] Example 3:

[0079] The preparation process of CeV-HNA / NF differs from that in Example 1 in that the molar concentration of cerium ammonium nitrate solution was adjusted to 0.6 mol / L during the etching process. -1 4.932 g of cerium ammonium nitrate was dissolved in 15 mL of deionized water, with other steps identical to those in Example 1. The electrochemical performance testing of the prepared electrocatalyst was conducted in the same manner as in Example 1. The results showed that when CeV-HNA / NF was used simultaneously as both the anode and cathode of the electrolyzer, it could drive the electrolysis of water to 10 mA cm⁻¹ at 1.58 V. -2 It outperforms commercially available Pt / C∥IrO2 and can be tested at 100 mA cm⁻¹. -2 It can maintain the stability of electrolyzed water for 150 hours under high current density.

[0080] Comparative Example 1:

[0081] Preparation of CeV-MOF / NF:

[0082] The preparation method of CeV-MOF / NF is the same as in Example 1, except that the molar concentration of cerium ammonium nitrate solution during the etching process is 0.3 mol / L. -1 .

[0083] Figure 10 This is a SEM image of the CeV-MOF / NF obtained in Comparative Example 1. Figure 10 It can be seen that the morphology of the obtained CeV-MOF / NF is the same as that of Ce-MOF / NF, and no hollow structure is formed.

[0084] Comparative Example 2:

[0085] Preparation of CeV-MOF / NF:

[0086] The synthesis steps for CeV-MOF / NF are the same as in Example 1, except that the molar concentration of cerium ammonium nitrate during the etching process is 0.7 mol / L. -1 .

[0087] Figure 11 This is a SEM image of the CeV-MOF / NF obtained in Comparative Example 2. Figure 11 It can be seen that the morphology and structure of the obtained CeV-MOF nanopillars were destroyed, and a regular hollow nanopillar array structure was not formed.

[0088] Comparative Example 3:

[0089] 0.568 g of ferric chloride hexahydrate, 0.61 g of nickel nitrate hexahydrate, 0.135 g of potassium hydroxide, and 0.498 g of terephthalic acid were dissolved in 60 mL of N,N-dimethylformamide (DMF) and magnetically stirred to obtain a homogeneous solution. The substrate NF was introduced into the above solution and reacted at 150 °C for 2 h. After cooling, the product was washed with ethanol and vacuum dried to obtain NiFe-MOF / NF. Then, cerium salt was used for etching, with the etching steps being the same as step (2) of Example 1. Finally, the product was processed according to the calcination process of Example 1 to obtain CeNiFe / NF.

[0090] The OER and HER performance of CeNiFe / NF were tested according to the electrochemical testing procedure in Example 1. Figure 12 and Figure 13 As shown, CeNiFe / NF at 50 mA cm -2 The overpotentials at the two levels were 310 mV and 252 mV, respectively, both greater than the corresponding overpotentials of CeV-HNA / NF (220 mV and 125 mV), indicating that their catalytic activity was not as good as that of the electrocatalytic material prepared in Example 1.

[0091] Comparative Example 4:

[0092] 3.6 g of dimethylimidazole and 0.126 g of cetyltrimethylammonium bromide were dissolved in 30 mL of water. Then, 3 mL of a solution containing 0.372 g of cobalt acetate tetrahydrate was mixed with the above solution to obtain a synthetic solution. The substrate NF was immersed in the above solution and reacted at 120 °C for 10 h. After washing with deionized water and drying, Co-MOF / NF was obtained. Then, cerium salt was used for etching treatment. The etching steps were the same as step (2) of Example 1. Finally, CeCo / NF was obtained by calcination treatment according to the process of Example 1.

[0093] The OER and HER performance of CeCo / NF were tested according to the electrochemical testing procedure in Example 1. Figure 12 and Figure 13 As shown, CeCo / NF at 50 mA cm -2 The overpotentials at the two locations were 420 and 313 mV, respectively, both greater than the corresponding overpotentials of CeV-HNA / NF (220 mV and 125 mV), indicating that their catalytic activity was not as good as that of the electrocatalytic material prepared in Example 1.

[0094] Comparative Example 5:

[0095] Under magnetic stirring, 0.233 g of ammonium metavanadate, 0.580 g of cobalt nitrate hexahydrate, and 0.466 g of terephthalic acid were dissolved in 50 mL of a mixed solution of DMF and H2O (volume ratio 1:1). Then, the substrate NF was introduced into the synthesis solution and heated at 180 °C for 6 h. The product was washed with deionized water and ethanol and dried under vacuum at 60 °C for 12 h to obtain VCo-MOF / NF. Finally, it was processed according to the calcination process of Example 1 to obtain VCo / NF.

[0096] Following the procedure in Example 1, the OER and HER performance of VCo / NF were tested. Figure 12 and Figure 13 As shown, VCo / NF at 50 mA cm -2 The overpotentials at these values ​​were 380 and 397 mV, respectively, both greater than the corresponding overpotentials of CeV-HNA / NF (220 mV and 125 mV), indicating that their catalytic activity was not as good as that of the electrocatalytic material prepared in Example 1.

[0097] In summary, in Comparative Example 1, the cerium salt concentration was low during etching, resulting in insufficient etching. In Comparative Example 2, the cerium salt concentration was high during etching, leading to over-etching and damage to the MOF nanopillar array structure. Neither of these conditions could yield a structurally complete CeV-MOF hollow nanopillar array, let alone a CeV-HNA / NF catalyst. In Comparative Examples 3-5, the catalysts obtained by combining Ce or V with Co, Ni, and Fe-based materials exhibited performance inferior to the electrocatalytic material obtained in Example 1 of this invention. Figure 3 The SEM images show that the hollow nanopillar array obtained in Example 1 has the most complete structure. It exhibits excellent performance when used alone as a self-supporting catalyst for HER and OER; when used simultaneously as the anode and cathode of an electrolyzer, it can drive water electrolysis to 10 mA cm⁻¹ at 1.52 V. -2 It outperforms commercially available Pt / C∥IrO2 and can withstand 100 mA cm⁻¹ -2 It maintains the stability of electrolyzed water for 150 hours under high current density.

[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material, characterized in that: The invention includes a substrate and a composite loaded on the substrate, wherein the composite forms a hollow nanopillar array structure on the substrate, and the composite includes CeO2, V8C7 and V2O5. The molar ratio of CeO2, V8C7 and V2O5 is (3~15):(10~40):(30~70); The substrate is nickel foam; The total loading of CeO2, V8C7, and V2O5 on the substrate was 1–5 mg cm⁻¹. -2 .

2. A method for preparing the cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material as described in claim 1, characterized in that, It includes the following steps: (1) The substrate was placed in a vanadium-based synthesis solution for in-situ growth, and a vanadium-based metal-organic framework (V-MOF) nanopillar array was formed on the substrate. (2) The substrate loaded with V-MOF nanopillar array was etched in an aqueous solution of cerium salt to obtain a substrate-supported CeV-MOF hollow nanopillar array. (3) The substrate loaded with CeV-MOF hollow nanopillar array was calcined in an inert gas atmosphere to obtain cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material. The vanadium-based synthesis solution comprises vanadium oxysulfate, a ligand, and deionized water; The ligand is terephthalic acid or aminoterephthalic acid.

3. The preparation method of the cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material according to claim 2, characterized in that: The molar ratio of vanadium sulfate, ligand, and deionized water is 1:1:(3500~4500).

4. The preparation method of the cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material according to claim 2, characterized in that: The molar concentration of cerium ions in the aqueous solution of the cerium salt is greater than 0.3 mol / L. -1 And less than 0.7 mol L -1 .

5. The method for preparing the cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material according to claim 2, characterized in that: The cerium salt is any one of cerium ammonium nitrate, cerium nitrate, cerium chloride, and cerium sulfate.

6. The method for preparing the cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material according to claim 2, characterized in that: The in-situ growth in step (1) is carried out at 150~170 ℃ for 45~75 h; the etching reaction in step (2) requires 6~18 h; the calcination in step (3) is carried out in an argon atmosphere at 550~650 ℃ for 2~5 h.

7. The application of the cerium-vanadium bimetallic hollow nanopillar array electrocatalytic material according to claim 1 in the electrocatalytic decomposition of water for oxygen and hydrogen evolution under alkaline conditions.